Indium-gallium-zinc oxide Schottky diodes on softening substrates for rectifying bioelectronic circuits. (1st September 2022) - Guerrero, Edgar; Rocha-Flores, Pedro Emanuel; Gutierrez-Heredia, Gerardo; Cogan, Stuart F; Voit, Walter E; Maeng, Jimin
Abstract: Incorporating electronic components onto soft materials facilitates the development of compliant electronics suited for bioelectronic applications. In this work, we present indium-gallium-zinc-oxide (IGZO) Schottky diodes fabricated on a stimuli-responsive polymer that undergoes softening (i.e. orders-of-magnitude drop in modulus) upon exposure to physiological stimuli. These diodes rectify megahertz radio-frequency (RF) signals in half-wave rectification circuits across the softening of the polymer substrate and withstand mechanical and chemical stresses such as repeated folding up to 10 000 cycles and aging in a simulated physiological medium for up to two weeks. The effects of thermal annealing and ultraviolet-ozone treatment processes are evaluated using dynamic mechanical analysis and x-ray photoelectron spectroscopy techniques, showing that these processes lead to a large improvement in the interface properties of the platinum-IGZO Schottky contact while preserving the thermomechanical properties of the softening polymer substrate. The RF rectification capabilities of these diodes in softened and deformed states are particularly interesting for the next generation of soft wireless bioelectronics.